Development and characterization of edible films from mixtures of κ-carrageenan, ι-carrageenan, and alginate. (May 2015) - Paula, Gabriela A.; Benevides, Norma M.B.; Cunha, Arcelina P.; de Oliveira, Ana Vitória; Pinto, Alaídes M.B.; Morais, João Paulo S.; Azeredo, Henriette M.C.
Abstract: Different proportions of κ-carrageenan, ι-carrageenan and alginate have been used to prepare glycerol-plasticized edible films, according to a simplex-centroid mixture design. κ-carrageenan was the component which most improved the moisture barrier and overall tensile properties (except elongation), while ι-carrageenan was the component which most impaired those properties. Alginate was the component which most favored film uniformity (as observed by SEM images) and transparency, while ι-carrageenan presented a high density of clusters and, accordingly, the highest effect on opacity. Aggregates in ι-carrageenan probably resulted from an early gelation induced either by the eventual presence of salt contaminants or by cooling the film dispersions to temperatures below 45 °C (coil-helix transition temperature of ι-carrageenan) upon casting. Those aggregates resulted in impaired physical (tensile, barrier, and optical) properties of films containing ι-carrageenan. Graphical abstract: Highlights: Films were prepared from κ-carrageenan, ι-carrageenan and alginate. κ-carrageenan was the component which most improved barrier and tensile properties. ι-carrageenan was the component which most impaired such properties. Alginate based films presented the highest uniformity and transparency. ι-carrageenan-containing films presented aggregates and high opacity.